Removal of Air-Drying Artifact of Papanicolaou Stained Smears with Normal Saline and Fresh Frozen Plasma - ., Lata; Kumari, Manju; Kolte, Sachin; Arora, Rashmi (Annals of Pathology and Laboratory Medicine, 2020)
Background Papanicolaou stained (Pap) smears in fine needle aspiration cytology play an important role for studying chromatin details of the cells and also ensures its optimal resemblance with the cell nuclei on histological sections. The conventional Pap Stained smears are ethanol fixed before drying. But delay in fixation due to any reason results in drying artifacts in the stained smears making it an inept smear for further examination. Aims & objectives: To study the role of rehydration fluid for removal of air drying artifact. Material and methods: Fifty fine needle aspiration smears from different organs with drying artifact in Pap Stained smears were included in the study. The smears were destained, rehydrated with rehydrating fluid for two hours and were restained with Pap stain after fixation with 95 % alcohol. Results : Smears treated with this solution showed reversal of the air drying artifact with better nuclear details and background material staining. Conclusion: Rehydration of destained Pap smears with rehydrating fluid followed by restaining results in optimal staining of the nuclear and background details preventing the material loss and making the smears appropriate for staining.